PENYEMPURNAAN PROSES REKONSILIASI MELALUI SAKTI: PENERAPAN METODE BUSINESS PROCESS IMPROVEMENT PADA AKUNTANSI PEMERINTAH PUSAT REPUBLIK INDONESIA - Davina Chairmanita (Universitas Islam Nahdlatul Ulama Jepara, 2023)
REFINING RECONCILIATION PROCESS THROUGH SAKTI: AN APPLICATION OF BUSINESS PROCESS IMPROVEMENT ON GOVERNMENT ACCOUNTING IN REPUBLIC OF INDONESIASAKTI full module Implementation as an integrated government accounting system, bring significant changes on reconciliation business process for state financial transactions. MonSAKTI reconciliation business process requires an improvement to be able to maximize the reporting process and minimize reconciliation time process. This study uses Business Process Modelling and Notation (BPMN) diagram to analyze and evaluate business process as-is and business process to-be and Business Process Improvement (BPI) to reform and enhance the performance of to existing business processes. The result from analyzing and evaluating business process as-is and business process to-be is improvement on real value added process, lessen on business value added process and eliminate non value added process, so the processing time is down to 33,33% and system complexity score reduce to 19,30%.